Text-to-Viz: Automatic Generation of Infographics from Proportion-Related Natural Language Statements - Cui, Weiwei; Zhang, Xiaoyu; Wang, Yun; Huang, Ray; Chen, Bei; Fang, Lei; Lou, Jian-Guang; Zhang, Haidong; Zhang, Dongmei (IEEE Transactions on Visualization and Computer Graphics, 2019)
Combining data content with visual embellishments, infographics can effectively deliver messages in an engaging and memorable manner. Various authoring tools have been proposed to facilitate the creation of infographics. However, creating a professional infographic with these authoring tools is still not an easy task, requiring much time and design expertise. Therefore, these tools are generally not attractive to casual users, who are either unwilling to take time to learn the tools or lacking in proper design expertise to create a professional infographic. In this paper, we explore an alternative approach: to automatically generate infographics from natural language statements. We ﬁrst conducted a preliminary study to explore the design space of infographics. Based on the preliminary study, we built a proof-of-concept system that automatically converts statements about simple proportion-related statistics to a set of infographics with pre-designed styles. Finally, we demonstrated the usability and usefulness of the system through sample results, exhibits, and expert reviews.